Elaboración de un jarabe de cebolla a partir de un extracto fluido con propiedades antitusivas y antiexpectorantes - Galarza Ramiréz, Bairon A. (2013)
This study aimed to develop pan anion- based syrup antitussive and expectorant useful as presenting a natural alternative to combat count, flu and other respiratory diseases are always present i our country and the World at large.